Compact multiband antenna for GPS/WiMAX/WLAN applications. Issue 8 (August 2015) - Chen, Shaojian; Fang, Mengli; Dong, Dacheng; Han, Mengqi; Liu, Gui
ABSTRACT: A compact microstrip‐fed multiband planar antenna for global positioning system, worldwide interoperability for microwave access, and wireless local area network applications is presented. Three operating frequency bands are achieved by a pair of L‐shaped slots and rectangular slots, and defected ground structure. The fabricated prototype for the proposed antenna occupies an area of 32 × 22.6 mm 2 . The measured results show that the proposed antenna has 10 dB impedance bandwidth of 420 MHz (1.34–1.76 GHz), 590 MHz (3.21–3.80 GHz), and 1.5 GHz (5.05–6.55 GHz). The proposed antenna shows good radiation patterns and acceptable gain over three operating bands. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:1769–1773, 2015